Pemenuhan Hak Pendidikan Anak Korban dari Eksploitasi Orang Tua - Yanti Mulyawati; Abdul Rohman (UPT Publikasi Ilmiah Unisba, 2024)
Abstract The case of exploitation of school-age children is contrary to the State's objectives, which are stated in the fourth paragraph of the Preamble to the 1945 Constitution of the Republic of Indonesia, namely to make the nation's life intelligent. Apart from that, regulations regarding the importance of fulfilling the rights of children at school age are regulated in Law number 35 of 2014 concerning Child Protection (Child Protection Law), which states that every child has the right to receive education and teaching in the context of their personal development and level of intelligence in accordance with interest and talent. The majority of the population in Indonesia is from a Muslim background, whose teachings place great importance on fulfilling children's rights, apparently this is not a guarantee as a solution to the success of the country's goals in Indonesia. In connection with this, the author is very interested in researching it with the thesis research title